2017
DOI: 10.1037/per0000205
|View full text |Cite
|
Sign up to set email alerts
|

Ecological momentary assessment of nonsuicidal self-injury in youth with borderline personality disorder.

Abstract: Nonsuicidal self-injury (NSSI) is highly prevalent among individuals with borderline personality disorder (BPD). The aim of this study was to investigate the cognitive, emotional, and contextual experience of NSSI in 107 youth (aged 15-25 years) with BPD who had minimal prior exposure to treatment. Using ecological momentary assessment, participants completed a randomly prompted questionnaire about their affect, self-injurious thoughts, and behaviors six times per day for 6 days. Twenty-four youth with BPD eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 51 publications
6
55
0
Order By: Relevance
“…Antisocial (31.8%) followed by avoidant (23.4%) and paranoid personality disorder (20.6%) were the three most commonly co‐occurring personality disorders. For further details on demographics, see Andrewes, Hulbert, Cotton, Betts, and Chanen ().…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antisocial (31.8%) followed by avoidant (23.4%) and paranoid personality disorder (20.6%) were the three most commonly co‐occurring personality disorders. For further details on demographics, see Andrewes, Hulbert, Cotton, Betts, and Chanen ().…”
Section: Resultsmentioning
confidence: 99%
“…Recall biases are unavoidable when using the SASII to identify NSSI and suicide attempts over the previous 12 months. Future studies investigating relative changes in these variables could overcome this problem by using techniques such as ecological momentary assessment (Andrewes et al, 2016).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Of note, more research is warranted investigating the potential utility of positive affect as a protective factor against NSSI, as evidence to date has yielded inconclusive results. While some researchers have observed a decrease in positive affect in the hours prior to engagement in NSSI (36,37), others failed to confirm such a time trend (38), and found that lower-than-usual positive affect is not prospectively predictive of NSSI (39,40). It may be that momentary lowered positive affect is more tolerable than increased negative affect, and therefore less relevant in eliciting NSSI (40).…”
Section: Affective Disturbances and Nssimentioning
confidence: 97%
“…Unfortunately, fewer studies have focused on the role of affect in determining short-term risk for NSSI at the within-person level [for an overview see (35)]. One consistent finding across studies is that negative affect increases prior to NSSI (36)(37)(38), and predicts a higher probability of NSSI in the next hours (39)(40)(41)(42). For instance, using ecological momentary assessment, Kranzler and colleagues observed that a momentary increase in negative affect positively predicted NSSI in the following 2-3 hours for adolescents and young adults (40).…”
Section: Affective Disturbances and Nssimentioning
confidence: 99%
“…Finally, another factor that can play a role in NSSI is intense negative affect [49], which has been associated with increased odds for NSSI [19,50]. Many studies found a decrease of negative affect after NSSI (e.g., [51]), partly in combination with increased negative affect prior to NSSI [52]; yet negative affect may also increase following NSSI [53]. Positive affect tended to decrease before and increase after acts of NSSI [54].…”
Section: Entrapment and Negative Affectmentioning
confidence: 99%